Treatment of a Rare Bilateral Sever Ectopic Eruption of the Maxillary First Permanent Molar: A Case Report - MS. Ahmad Akhoundi; AH. Sadrhaghighi (Tehran University of Medical Sciences, 2009)
A 7.5 year-old girl was seeking orthodontic treatment because of severe ectopic eruption of maxillary first permanent molars. It was a rare case that represented approximately horizontal view in panoramic radiograph. The severity of problem was high, but since the patient had maxillary deficiency, it was important to perform the treatment without extraction. Treatment began with extraction of upper deciduous second molars and continued with a modified Nance appliance. The period of treatment was 16 months and the result was excellent. This satisfactory outcome of treatment justifies clinicians to evaluate and diagnose this group